Hippocampal Malrotation Could Be Less Significant in Epilepsy Caused by Focal Cortical Dysplasia Type I and Type II - He, Chenmin; Ye, Lingqi; Chen, Cong; Hu, Lingli; Jin, Bo; Ding, Yao; Li, Hong; Ding, Meiping; Wang, Shan; Wang, Shuang (Frontiers in Neurology, 2022)
Objectives Debates over the relationship between hippocampal malrotation (HIMAL) and epilepsy continue without consensus. This study explores the role of HIMAL in a cohort of epilepsy caused by focal cortical dysplasia (FCD). Methods: Ninety patients with epilepsy caused by FCD type I and type II and 48 healthy adults underwent a 3 Tesla MRI following a dedicated epilepsy protocol for the analysis of the prevalence and morphologic features of HIMAL. Numerous clinical characteristics and hippocampal volumes were also evaluated. Results: The cohort included a total of 90 patients (32 were HIMAL, 58 were non-HIMAL). Among these patients, 32 (35.6%) had HIMAL (22 left, 4 right, and 6 bilateral), which did not differ from the 48 controls, where 16 (33.3%) had HIMAL (12 left, 2 right, and 2 bilateral). Neither the quantitative features of HIMAL (diameter ratio, dominant inferior temporal sulcus height ratio, medial distance ratio, dominant inferior temporal sulcus angle, and parahippocampal angle), nor the accompanying characteristics of HIMAL (vertical dominant inferior temporal sulcus, enlarged temporal horn, and a low position of ipsilateral fornix) showed differences between FCD patients and controls. No statistical difference in the clinical characteristics between FCD patients with HIMAL and those without was found. Neither the side nor the existence of HIMAL was correlated with the lateralization and location of FCD. As to the hippocampal volume, there was no difference between FCD patients with HIMAL and those without. Conclusion: HIMAL is a common morphologic variant in healthy controls as well as in patients with epilepsy caused by FCD type I and type II. Hippocampal malrotation could be less significant in epilepsy caused by FCD type I and type II.